2023
DOI: 10.1097/rhu.0000000000001953
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Associations of Children With Familial Mediterranean Fever in a Cohort Consisting of M694V Mutation and Implications for Colchicine-Resistant Disease

Abstract: ObjectivesThe aim of this study was to investigate the clinical associations of the second allele mutations and the effect of genotype and presenting features on colchicine resistance in children with familial Mediterranean fever (FMF), carrying at least one M694V variant.MethodsThe medical records of the patients diagnosed with FMF, in whom at least one allele M694V mutation was detected, were reviewed. Patients were grouped according to the genotype as M694V homozygotes, compound heterozygote M694V with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…showed that clinical features such as fever, abdominal pain, chest pain, arthritis and erysipelas-like erythema did not differ according to the homozygous or heterozygous M694V mutation [27]. However, in an adult study published by Balta et al, FMF patients revealed genotype-phenotype correlation, and fever was most prevalent in patients with homozygous exon 10 mutations [28].…”
Section: Discussionmentioning
confidence: 99%
“…showed that clinical features such as fever, abdominal pain, chest pain, arthritis and erysipelas-like erythema did not differ according to the homozygous or heterozygous M694V mutation [27]. However, in an adult study published by Balta et al, FMF patients revealed genotype-phenotype correlation, and fever was most prevalent in patients with homozygous exon 10 mutations [28].…”
Section: Discussionmentioning
confidence: 99%